Implementation of the Merdeka Curriculum in Islamic Religious Education and Its Impact on Students’ Learning Autonomy at SMA Negeri 2 Sarolangun - Nelly Setia Wati; Sukiman Sukiman; Khairul Abdillah Harahap; Sofia Yunus Putri; Agus Alfaya Arif (Yayasan Pendidikan Bima Berilmu, 2026)
This study aims to analyze the implementation of the Merdeka Curriculum in Islamic Religious Education and its impact on student learning independence at the high school level. This study uses a qualitative approach with a case study design at SMA Negeri 2 Sarolangun. Data were collected through participatory observation, in-depth interviews, and documentation analysis, then analyzed using an interactive model that included data reduction, data presentation, and verification through triangulation. The results showed that the implementation of the Merdeka Curriculum was reflected in competency-based planning, diagnostic assessment, differentiated learning, and contextual project integration. This transformation encourages an increase in student learning independence, which is seen in the aspects of learning initiative, self-regulation, and metacognitive reflection. Project-based learning and reflective assessment play an important role in strengthening academic responsibility and learning awareness. However, variations in intrinsic motivation and limited facilities are challenges in optimizing implementation. This study confirms that the Merdeka Curriculum has significant potential in developing self-regulated learning in Islamic Religious Education. These findings have practical implications for the development of more autonomous, reflective, and contextual learning strategies in secondary schools.